Effectiveness of Duration Time to Use the Digital Dental Calculator Application on DMFT Index Measurement - Mariana, Ireny; Fadriyanti, Okmes; Ningrum, Valendriyani (Indonesian Dental Association, 2024)
Introduction: Caries is a dental and oral disease characterized by cavities. To assess the severity of caries using an index, namely the DMFT (Decayed Missing Filled Tooth) index. The DMFT index is often used to monitor oral health status in the community. The results of the DMFT Index examination have often been calculated manually using paper and pen, so the time required is longer. Along with the development of technology, a digital dental calculator application was developed as a solution to shorten the duration and increase the accuracy of the DMFT Index calculation results. Objective: To determine the effectiveness of the digital dental survey application on the duration of DMFT index measurement time. Methods: This type of research is a Quasi Experiment with Post-test Only Group Design. The sampling technique used convenience sampling with a total of 64 professional students at Baiturrahmah Dental Hospital who met the inclusion and exclusion criteria. Results: The average time for the sample to measure the DMFT index manually was 220.81 seconds while the digital measurement was 30.17 seconds. The Mann Whitney test results showed a significant difference in time duration (p<0.05) between the use of digital dental applications and manual in measuring the DMFT Index. DMFT Index calculation using the application is shorter than the manual calculation. Conclusion: The digital dental calculator application is more effective in shortening the duration of time compared to manual calculations in calculating the DMFT Index results.